Peningkatan Kemandirian Keuangan Kelompok Wanita Tani Melalui Pendekatan Berjejaring di Daerah Sudiang Makassar - Yusra Nginang; Rukmana Sari; Asniwati Asniwati; Jessica Titaley (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service activity aims to increase the financial independence of the Women Farmers Group (KWT) in Sudiang, Makassar, through a networking approach and strengthening financial literacy capacity. The main problems faced by the local KWT are the still low understanding of group financial management, limited access to financial information, and dependence on external assistance. Through socialization, training, and interactive discussions, participants were provided with an understanding of the basic concepts of financial independence, simple financial record keeping, collective fund management, and the importance of institutional networks as a sustainability strategy. The results of the activity showed an increase in members' understanding of the importance of financial literacy and the ability to design an internal financial system independently. In addition, strengthening networks with local stakeholders was also started as a first step towards finding a KWT business. The activity concluded with a question and answer session and the presentation of certificates to participants as a form of appreciation and ongoing motivation. Going forward, further mentoring is needed so that the empowerment process can continue to develop consistently. As a follow-up to this activity, a sustainable mentoring strategy is needed so that the understanding and skills that have been acquired do not just stop at the level of knowledge, but can be implemented in real life in the KWT's daily activities. This mentoring can include monitoring the group's financial records, facilitating access to microfinance institutions, and training in building partnerships with external parties such as government, academics, and the private sector. With structured mentoring, KWT is expected to be able to build a transparent and accountable financial management system and support the growth of sustainable, productive businesses. This aligns with efforts to strengthen women's independence in the agricultural sector while contributing to the welfare of families and the wider community.